2021
DOI: 10.1111/cea.14023
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity may be involved in severe COVID‐19

Abstract: Background Deaths attributed to Coronavirus Disease 2019 (COVID‐19) are mainly due to severe hypoxemic respiratory failure. Although the inflammatory storm has been considered the main pathogenesis of severe COVID‐19, hypersensitivity may be another important mechanism involved in severe cases, which have a perfect response to corticosteroids (CS). Method We detected the serum level of anti‐SARS‐CoV‐2–spike S1 protein‐specific IgE (SP‐IgE) and anti‐SARS‐CoV‐2 nucleocaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…It is known that the SARS‐CoV‐2 infection induces complement activation, which could activate basophils. Furthermore, anti‐SARS‐CoV‐2‐specific IgE and mast cells with positive staining for IgE and CD63 were observed in patients with severe SARS‐CoV‐2 infections 34 . Experiments with the BAT showing a decrease in BNT‐vaccine‐induced basophil activation by preincubation with wortmannin might pose an argument for an IgE‐mediated immune response to SARS‐CoV‐2 spike proteins in patients with a previous SARS‐CoV‐2 infection 28 .…”
Section: Evaluation Of the Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…It is known that the SARS‐CoV‐2 infection induces complement activation, which could activate basophils. Furthermore, anti‐SARS‐CoV‐2‐specific IgE and mast cells with positive staining for IgE and CD63 were observed in patients with severe SARS‐CoV‐2 infections 34 . Experiments with the BAT showing a decrease in BNT‐vaccine‐induced basophil activation by preincubation with wortmannin might pose an argument for an IgE‐mediated immune response to SARS‐CoV‐2 spike proteins in patients with a previous SARS‐CoV‐2 infection 28 .…”
Section: Evaluation Of the Studiesmentioning
confidence: 97%
“…Furthermore, anti‐SARS‐CoV‐2‐specific IgE and mast cells with positive staining for IgE and CD63 were observed in patients with severe SARS‐CoV‐2 infections. 34 Experiments with the BAT showing a decrease in BNT‐vaccine‐induced basophil activation by preincubation with wortmannin might pose an argument for an IgE‐mediated immune response to SARS‐CoV‐2 spike proteins in patients with a previous SARS‐CoV‐2 infection. 28 BATs with spike peptides showed a slightly higher activation compared to baseline (below the cut‐off) in some patients with previous SARS‐CoV‐2 infection, which could be a hint for such a mechanism.…”
Section: Evaluation Of the Studiesmentioning
confidence: 99%
“…DAD is also observed in lungs of patients ADRS, acute hypersensitivity pneumonitis, idiopathic acute interstitial pneumonia, drug abuse, toxic inhalants, ingestants, connective tissue disease, viral and bacterial infections including some acute forms of tuberculosis ( 52 , 53 ). In addition, the levels of serum anti-SARS-CoV-2–spike S1 protein-specific IgE (SP-IgE) and anti-SARS-CoV-2 nucleocapsid protein-specific IgE (NP-IgE) appear to be significantly higher in patients suffering severe COVID-19; and SP-IgE levels correlated with the total lung severity scores and the ratio of arterial oxygen partial pressure to fractional inspired oxygen (PaO 2 /FiO 2 ) ( 54 ). Post-acute sequalae COVID-19 patients report significantly higher expression in serum of IL-6 and CXCL1; whereas no difference was observed on serum levels of IL-8, TNF, CCL2, CCL3, IL-17A, IL-33, and VEGF ( 55 ).…”
Section: Mcs In Lung Diseasesmentioning
confidence: 99%
“…23 Other studies demonstrated that severe COVID-19 disease is associated with robust inflammatory responses including type two and hyper four hypersensitivity responses, resulting from overactivation of T cells and a subsequent cytokine storm. 24,25 manifestations of COVID-19 include mimicry of autoimmune diseases like Kawasaki disease, Guillain-Barre syndrome, vasculitis, myositis, and myocardial damage. 26 Puntmann et al found a 78% cardiac involvement assessed by Cardiac Magnetic Resonance Imaging (MRI) among patients with a confirmed diagnosis of COVID-19 eight weeks before enrollment 27 , most of whom were asymptomatic or had just mild symptoms.…”
Section: Discussionmentioning
confidence: 99%